2022
DOI: 10.1038/s41598-022-13133-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of colchicine use on ischemic and hemorrhagic stroke risk in diabetic patients with and without gout

Abstract: This study aimed to determine the effect of colchicine use on the risk of stroke among patients with diabetes mellitus (DM). We retrospectively enrolled patients with DM between 2000 and 2013 from the Longitudinal Health Insurance Database and divided them into a colchicine cohort (n = 8761) and noncolchicine cohort (n = 8761) by using propensity score matching (PSM). The event of interest was a stroke, including ischemic stroke and hemorrhagic stroke. The incidence of stroke was analyzed using multivariate Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Recent clinical trials targeting GPVI either directly with ACT017, Voors-Pette et al ( 10 ) or indirectly with Revacept, Uphaus et al ( 9 ) have shown great promise in reducing collagen-mediated platelet activation and improved stroke outcome without leading to bleeding complications ( 64 ). Colchicine reduces the risk of hemorrhagic and ischemic stroke ( 65 67 ), which is consistent with the reduction observed for Revacept both in a mouse stroke model ( 36 ) and a human carotid stenosis clinical trial ( 9 ), however colchicine has additional anti-inflammatory affects. Like ACT017 and Revacept, colchicine treatment has not been linked to bleeding complications.…”
Section: Discussionsupporting
confidence: 78%
“…Recent clinical trials targeting GPVI either directly with ACT017, Voors-Pette et al ( 10 ) or indirectly with Revacept, Uphaus et al ( 9 ) have shown great promise in reducing collagen-mediated platelet activation and improved stroke outcome without leading to bleeding complications ( 64 ). Colchicine reduces the risk of hemorrhagic and ischemic stroke ( 65 67 ), which is consistent with the reduction observed for Revacept both in a mouse stroke model ( 36 ) and a human carotid stenosis clinical trial ( 9 ), however colchicine has additional anti-inflammatory affects. Like ACT017 and Revacept, colchicine treatment has not been linked to bleeding complications.…”
Section: Discussionsupporting
confidence: 78%
“…The included study by Jun-Jun Yeh et al 9 is a retrospective cohort study that aimed to investigate the effect of colchicine use on the risk of stroke among patients with diabetes mellitus. The study was conducted between 2000 and 2013 and enrolled a total of 17,522 patients with diabetes mellitus from the Longitudinal Health Insurance Database.…”
Section: Resultsmentioning
confidence: 99%
“…However, the study found that colchicine was not associated with hemorrhagic stroke in DM patients without gout. 9 …”
Section: Results Interpretationmentioning
confidence: 99%